1994
DOI: 10.3168/jds.s0022-0302(94)77079-x
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effects of Dietary β-Carotene on Blood and Mammary Leukocyte Function in Periparturient Dairy Cows

Abstract: Beginning 4 wk prior to predicted calving, 14 Holstein cows per treatment were fed diets 1) unsupplemented (control) or supplemented daily with 2) 300 mg of beta-carotene, 3) 600 mg of beta-carotene, or 4) 120,000 IU of vitamin A. Blood was collected around calving on wk -4, -2, -1, 0 (within 24 h postcalving), 1, 2, and 4 for isolation of lymphocytes and neutrophils and for the analysis of plasma vitamins. Lacteal secretions were collected on wk 0, 1, 2, and 4 for the isolation of phagocytes. Cows supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
2
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 22 publications
5
50
2
2
Order By: Relevance
“…The results indicate that the most useful method, with highest % of cells are Ficoll and Histopaque. The results are similar to those obtained by Michal et al (1994). The experiments showed that the isolation methods had an influence on the viability of leukocytes.…”
Section: Resultssupporting
confidence: 87%
“…The results indicate that the most useful method, with highest % of cells are Ficoll and Histopaque. The results are similar to those obtained by Michal et al (1994). The experiments showed that the isolation methods had an influence on the viability of leukocytes.…”
Section: Resultssupporting
confidence: 87%
“…The two T-cell mitogens reflect the general cellular immune responsiveness of the organism. The results of this experiment correspond to data given in a number of reports in the literature, according to which both nucleotide and P-carotene supplementation result in an increase in T-cell immune responsiveness (Bendich and Shapiro, 1986;Barankiewicz and Cohen, 1987;Perignon et al, 1987;Hoskinson et al, 1989;Daniel et al, 1991 a,b;Michal et al, 1994). P-carotene is deposited in the lymphocytes, and acts as an immunostimulator partly by virtue of its effect on membrane protection and partly via promoting blastogenesis (Chew et al, 1993).…”
Section: Resultssupporting
confidence: 86%
“…The addition of low concentrations of β-carotene to bovine lymphocyte cultures also stimulated mitogen-induced blastogenesis (Daniel et al 1991). Supplementation of β-carotene did not consistently affect neutrophil bactericidal activity (Michal et al 1994).…”
Section: Cobaltmentioning
confidence: 95%